2002
DOI: 10.1034/j.1600-0447.2002.02245.x
|View full text |Cite
|
Sign up to set email alerts
|

The Danish PET/depression project: clinical symptoms and cerebral blood flow. A regions‐of‐interest analysis

Abstract: Our findings support the notion that depressed patients have disturbances in the loops connecting the frontal lobes, limbic system, basal ganglia, and cerebellum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(91 citation statements)
references
References 70 publications
5
82
3
Order By: Relevance
“…25 Similarly, other studies have found that men appear to be more vulnerable to the adverse impacts of depressive syndromes on cognitive functioning and brain integrity. 33,34 We did not find such a sex difference in the present study. This may be due at least in part to statistical power since the number of men in our sample, particularly in the incident dementia analysis, was smaller than the number of women.…”
Section: Figure 2 Kaplan-meier Survival Curve Of Time To Incidence Ofcontrasting
confidence: 51%
“…25 Similarly, other studies have found that men appear to be more vulnerable to the adverse impacts of depressive syndromes on cognitive functioning and brain integrity. 33,34 We did not find such a sex difference in the present study. This may be due at least in part to statistical power since the number of men in our sample, particularly in the incident dementia analysis, was smaller than the number of women.…”
Section: Figure 2 Kaplan-meier Survival Curve Of Time To Incidence Ofcontrasting
confidence: 51%
“…Increases in neural activity in similar regions of the ACC have been observed during depression (Kennedy et al, 2001;Videbech et al, 2002) and experimentally induced sadness (eg George et al, 1995;Liotti et al, 2000), and baseline activity in this region has been shown to predict response to antidepressant treatment (Mayberg et al, 1997Pizzagalli et al, 2001). In addition, higher glucose metabolism and perfusion in perigenual aspects of the ACC have been found to be positively correlated with both severity of depression and psychomotor retardation (Ebmeier et al, 1997;Dunn et al, 2002).…”
Section: Increased Mdlfc-acc Connectivity and Pitch Variation In Speechmentioning
confidence: 84%
“…Neurological disorders affecting the basal ganglia or the cerebellum are associated with depressive symptoms (Afifi 2003;Konarski et al 2005). Hypometabolism in the basal ganglia has been reported in depressed patients (Videbech et al 2002). Hypermetabolism and increased perfusion in the cerebellum have been reported in healthy subjects during induced sadness paradigms, as well as in depressed patients during resting states (Videbech et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Hypometabolism in the basal ganglia has been reported in depressed patients (Videbech et al 2002). Hypermetabolism and increased perfusion in the cerebellum have been reported in healthy subjects during induced sadness paradigms, as well as in depressed patients during resting states (Videbech et al 2002). In depressed patients, response to antidepressant treatment has been associated with changes in blood flow and metabolic activity in the cerebellum (Holthoff et al 2004;Mayberg et al 2000).…”
Section: Discussionmentioning
confidence: 99%